EARLY PREGNANCY DIAGNOSIS IN CORRIEDALE SHEEP BY REALTIME B-MODE ULTRASONOGRAPHY - GANAIE, B A; KHAN, M Z; MAKHDOOMI, D M; ISLAM, R; WANI, G M (The Indian Journal of Animal Reproduction, 2023)
Fifty Corriedale ewes were scanned in dorsal recumbency for pregnancy diagnosis using realtimeB-mode ultrasonic equipment provided with a 3.5 MHz sector array transducer at 15 days intervalstarting from 15 days post tupping upto lambing through trans-abdominal approach. The accuracy,sensitivity, specificity and the prediction values of the technique were evaluated at the different stagesof gestation, by comparing the ultrasonic results with lambing records and noticeable abortions. Anaccuracy of 68% and a sensitivity of 70A% were observed at Day 27 .0 ± 0.83 ( 15-30), which increasedsignificantly (P
Keywords: Early pregnancy diagnosis; Sheep, B-mode ultrasonography